Using local stiffness indicator to examine the effect of honeycombs on the flexural stiffness of reinforced concrete beams - Monajemi, H.; Mazinani, I.; Chao, O.Z.; Yee, K.S.; Kuan, K.K.; Karim, R. (2015)
Experimental modal analysis was performed on RC beams with honeycombs. The mode shapes were extracted, and the eigenvectors were used in determining the mode shape equations using nonlinear regression. The equation used in the regression was the generalized solution of transverse vibration of a Bernoulli-Euler prismatic beam. By utilizing the regressed phase variable, the global flexural stiffness was evaluated. It was observed that the global stiffness dropped with increasing volumes of the honeycombs in the beam. The results were compared with values computed using the secant modulus from the load-deflection plot obtained upon loading at each load stage and the trend was similar. The local stiffness indicator was used successfully to locate the region of the honeycombs. (C) 2015 Elsevier Ltd. All rights reserved.